Multicriteria evaluation of apartment blocks maintenance contractors: Lithuanian case study - Zavadskas, Edmundas Kazimieras; Kaklauskas, Artūras; Vilutienė, Tatjana (International Journal of Strategic Property Management, 2009)
The paper presents the comparative analysis of dwelling maintenance contractors aimed at determining the degree of their utility for users and bidding price of services by applying the method of multicriteria complex proportional assessment. To compare the performance of various maintenance contractors, the data from 15 dwelling maintenance organizations was used. A questionnaire survey of dwelling owners was conducted. Contractors were evaluated by a set of 44 criteria characterizing them from various perspectives. The analysis was made taking into account the standpoints of building owners (clients). The initial weights of qualitative criteria were calculated by expert methods. Then they were coordinated with the calculated values of quantitative criteria using the method of multicriteria complex proportional assessment. Multicriteria analysis of the performance of maintenance contractors allows us to determine the importance of particular contractor characteristics for achieving the aim to meet the needs of different participants of the maintenance process. First Publish Online: 18 Oct 2010